Parkia speciosa Hassk. Empty Pod Extract Alleviates Angiotensin II-Induced Cardiomyocyte Hypertrophy in H9c2 Cells by Modulating the Ang II/ROS/NO Axis and MAPK Pathway - Siti, Hawa Nordin; Jalil, Juriyati; Asmadi, Ahmad Yusof; Kamisah, Yusof (Frontiers in Pharmacology, 2021)
Cardiac hypertrophy is characteristic of heart failure in patients who have experienced cardiac remodeling. Many medicinal plants, including Parkia speciosa Hassk., have documented cardioprotective effects against such pathologies. This study investigated the activity of P. speciosa empty pod extract against cardiomyocyte hypertrophy in H9c2 cardiomyocytes exposed to angiotensin II (Ang II). In particular, its role in modulating the Ang II/reactive oxygen species/nitric oxide (Ang II/ROS/NO) axis and mitogen-activated protein kinase (MAPK) pathway was examined. Treatment with the extract (12.5, 25, and 50 µg/mL) prevented Ang II-induced increases in cell size, NADPH oxidase activity, B-type natriuretic peptide levels, and reactive oxygen species and reductions in superoxide dismutase activity. These were comparable to the effects of the valsartan positive control. However, the extract did not significantly ameliorate the effects of Ang II on inducible nitric oxide synthase activity and nitric oxide levels, while valsartan did confer such protection. Although the extract decreased the levels of phosphorylated extracellular signal-related kinase, p38, and c-Jun N-terminal kinase, valsartan only decreased phosphorylated c-Jun N-terminal kinase expression. Phytochemical screening identified the flavonoids rutin (1) and quercetin (2) in the extract. These findings suggest that P. speciosa empty pod extract protects against Ang II-induced cardiomyocyte hypertrophy, possibly by modulating the Ang II/ROS/NO axis and MAPK signaling pathway via a mechanism distinct from valsartan.